Home and Neighbourhood Built Environment Latent Class Profiles and Young Children’s Developmental Vulnerability: Findings from the Australian Early Development Census - Christian, Hayley; Adams, Emma; Zhao, Mingxuan; Villanueva, Karen; Brinkman, Sally; Schipperijn, Jasper; Boruff, Bryan; Francis, Jacinta (International Journal of Population Data Science, 2026)
Introduction Children's developmental outcomes in their early years have lifelong consequences for later health and wellbeing. Despite persistent geographical inequities in early development, the specific role of the neighbourhood built environment remains underexplored. Understanding how different neighbourhood typologies influence early development can inform more equitable urban planning and policy for children. Objectives To identify typologies of neighbourhood built environments and assess their association with early childhood developmental vulnerability, and whether these associations differ by area-level disadvantage. Methods Australian Early Development Census (AEDC) data were linked with geospatial measures of the neighbourhood built environment for 5,066 children in Perth, Western Australia. Latent profile analysis identified neighbourhood built environment profiles based on features such as access to green space, movement network, and child-relevant destinations. Logistic regression models tested associations between built environment profiles and developmental vulnerability, stratified by area-level disadvantage. Results Overall, 21.8% of children were developmentally vulnerable on at least one AEDC domain. Five built environment profiles emerged: 'Average neighbourhood', 'Established neighbourhood', 'Low destinations and transport mix', 'Connected housing', and 'Disconnected semi-rural'. Children in the 'Established neighbourhood' profile had significantly lower odds of developmental vulnerability (18.3%) compared with 'Average neighbourhood', 'Connected housing', and 'Disconnected semi-rural' profiles. In more disadvantaged areas, associations between built environment profiles and developmental vulnerability were less consistent. Conclusions Neighbourhoods with better access to child-relevant destinations, attractive green spaces, and public transport were associated with lower developmental vulnerability. Conversely, neighbourhoods with a substandard movement network, less destination access, and higher traffic exposure were linked to worse early development outcomes. Further studies should focus on unpacking the mechanisms through which individual and combined effects of features of the neighbourhood environment influence early development.